2018
DOI: 10.3847/1538-4357/aaccff
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Destruction of SiS in Space

Abstract: The presence of SiS in space seems to be restricted to a few selected types of astronomical environments. It is long known to be present in circumstellar envelopes around evolved stars and it has also been detected in a handful of star-forming regions with evidence of outflows, like Sgr B2, Orion KL and more recently L1157-B1. The kinetics of reactions involving SiS is very poorly known and here we revisit the chemistry of SiS in space by studying some potentially important reactions of formation and destructi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…since the work of Podio et al (2017) and found to be plausible (Rosi et al 2018;Zanchet et al 2018;Rosi et al 2019).…”
Section: Discussionmentioning
confidence: 93%
“…since the work of Podio et al (2017) and found to be plausible (Rosi et al 2018;Zanchet et al 2018;Rosi et al 2019).…”
Section: Discussionmentioning
confidence: 93%
“…This assumption has been made on the basis of reproducing the interferometer observations of the region where photochemistry occurs (Agúndez et al 2017, and references therein). Particularly for the three species analysed in this work, we updated two important reactions in the chemistry of SiS according to Zanchet et al (2018), which are the destruction of SiS with atomic oxygen and the reaction between Si and SO. For the photo-dissociation rates of the studied species we took the values from Pattillo et al (2018) for CS and from Heays et al (2017) for SiO.…”
Section: Chemistrymentioning
confidence: 99%
“…Astrochemical models postulate the formation of silicon monosulfide is linked to reactions of interstellar anions with the silicon monosulfide cation (SiS + ), proton transfer from protonated silicon monosulfide (HSiS + ), and dissociative recombination of protonated silicon monosulfide with an electron ( 35 ). Alternatively, radiative associations between atomic silicon and sulfur ( 36 ) along with bimolecular collisions of atomic silicon with the thioxydroxyl radical (SH) ( 37 ) and with sulfur monoxide (SO) ( 38 , 39 ) have been assumed to initiate the formation of the first silicon-sulfur bond. Considering that none of the aforementioned postulated pathways to silicon monosulfide have been explored in laboratory studies, it is not unexpected that astrochemical models underestimate the astronomical observed fractional abundances of silicon monosulfide by up to two orders of magnitude ( 30 ).…”
Section: Introductionmentioning
confidence: 99%